People with dementia and caregiver preferences for digital life story work service interventions. A discrete choice experiment and digital survey. (1st February 2020) - O'Philbin, Laura; Woods, Bob; Holmes, Emily
Abstract: Objectives: Little is understood about the optimal way to implement digital life story work (LSW). The aim of this research was to explore the preferences of people with dementia and caregivers in relation to digital LSW in an effort to improve future engagement. Methods: 67 caregivers responded to an online discrete choice experiment (DCE) survey containing 16 pairwise choices. The DCE was analysed using a random effects logit model. Willingness to pay and odds ratios were also calculated. 17 participants with dementia completed an online survey in which they made choices about different aspects of digital LSW services. Results: Caregivers valued four out of five attributes [setting ( p  = 0.000), price ( p  = 0.000), elementary usability and accessibility ( p  = 0.001), and follow-up assistance ( p  = 0.034)]. In data from participants with dementia, the most preferred setting was individual one-to-one (70.6%), and the most preferred use of digital life storybooks was to share memories with others (64.7%). Marginally more participants with dementia said they would pay for the service (53%) rather than only use it free of charge (47%). Those with advanced ICT skills preferred to learn how to use the digital life storybook (64.7%), while those with elementary/intermediate skills, preferred to have it created for them (35.3%). Conclusions: This exploratory study provides an insight into preferences of people with dementia and caregivers, of how digital LSW is implemented. Results can contribute to future planning and tailoring of these services.